Analisis Pembingkaian Ketidakadilan dan Represi Politik Dalam Novel Laut Bercerita - Tryza Fatima Az Zahra; Choirul Ulil Albab (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Political injustice and repression often arise in authoritarian power systems and are often represented in literary works as a form of social criticism. This study aims to analyze the framing of injustice and political repression in the novel Laut Bercerita by Leila S. Chudori. The study uses a qualitative approach with a qualitative content analysis method. The analysis was conducted using the framing model of Zhongdang Pan and Gerald M. Kosicki which includes syntactic, script, thematic, and rhetorical structures. The research data consists of narratives and dialogues in the novel that describe the kidnapping, illegal detention, and torture of pro-democracy activists in the lead-up to the 1998 Reformation. The results show that the novel frames political repression as a systemic practice of state violence. The script structure displays a series of repeated violence, the syntactic structure positions activists as victims, the thematic structure emphasizes experiences of injustice and trauma, while the rhetorical structure strengthens meaning through metaphors and symbols. This novel functions as a social reflection as well as a critique of repressive power practices and the importance of protecting human rights.